LncRNA KCNQ1OT1 Promotes the Proliferation, Migration and Invasion of Retinoblastoma Cells by Upregulating HIF-1α via Sponging miR-153-3p. (December 2020) - Wang, Yujin; Wang, Jixiang; Hao, Hongyan; Luo, Xiangxia
It is reported that lncRNA KCNQ1 opposite strand/antisense transcript 1 (KCNQ1OT1) is oncogenic in many cancers. This work aimed at probing into its expression and biological functions in retinoblastoma (RB) as well as its regulatory effects on miR-153-3p and hypoxia-inducible factor-1α (HIF-1α). In our study, RB samples in pair were collected, and quantitative real-time PCR (qRT-PCR) was employed for examining the expression levels of KCNQ1OT1, miR-153-3p and HIF-1α. KCNQ1OT1 short hairpin RNAs were transfected into SO-Rb50 and HXO-RB44 cell to inhibit the expression of KCNQ1OT1. The proliferative activity, colony formation ability and apoptosis were examined through cell counting kit-8 assay, colony formation assays, Transwell assay and flow cytometry, respectively. qRT-PCR and western blot analysis were used for analyzing the changes of miR-153-3p and HIF-1α induced by KCNQ1OT1. The regulatory relationships between miR-153-3p and KCNQ1OT1, miR-153-3p and HIF-1α were examined by dual luciferase reporter gene assay and RNA-binding protein immunoprecipitation assay. The results of our study showed that KCNQ1OT1 expression was markedly enhanced in RB tissue samples, and KCNQ1OT1 knockdown had an inhibitory effect on the proliferation, migration, invasion and viability of RB cells. There were two validated binding sties between KCNQ1OT1 and miR-153-3p, and KCNQ1OT1 negatively regulated the expression of miR-153-3p in RB cells. HIF-1α was a target gene of miR-153-3p, and could be positively regulated by KCNQ1OT1. In conclusion, our study indicates that KCNQ1OT1 can increase the malignancy of RB cells via regulating miR-153-3p/HIF-1α axis.